An airway hemostatic aerogel and method of making same

CN122912173APending Publication Date: 2026-10-16HUNAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611073544.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]截至目前,在气道止血材料领域,尚未见有采用聚乳酸纤维与丝素蛋白纤维相互交织形成三维多孔网络结构,将止血材料分散于丝素蛋白纤维中,并通过纤维间黏结剂使两种纤维之间形成交联网络以增强湿态机械稳定性,且能在吸水膨胀后仍保持贯通孔隙结构以维持气道通气功能的气道止血气凝胶的相关报道

Benefits of technology

(1)本发明采用聚乳酸纤维与丝素蛋白纤维交织构成三维网络结构,并引入纤维间互锁黏结点形成稳定交联网络,显著提升气凝胶在湿态环境下的机械稳定性,长纤维的连续性可以保障透气性,同时赋予材料良好的生物相容性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912173A_ABST
    Figure CN122912173A_ABST
Patent Text Reader

Abstract

The application discloses an airway hemostatic aerogel and a preparation method thereof, and belongs to the technical field of biomedical materials. The aerogel is formed by interweaving polylactic acid fibers and silk fibroin fibers to form a three-dimensional porous network, interlocking bonding points are contained between the fibers, and hemostatic materials are dispersed in the silk fibroin fibers. The preparation method comprises the following steps: preparing polylactic acid spinning liquid, silk fibroin spinning liquid containing hemostatic materials and photosensitive adhesive solution; obtaining an interwoven assembly of polylactic acid fibers and silk fibroin fibers through rotary jet spinning, synchronously spraying the photosensitive adhesive and pre-curing under ultraviolet light, and then performing secondary ultraviolet setting, genipin crosslinking and gradient ethanol replacement. The hemostatic aerogel prepared by the method has excellent air permeability, rapid coagulation activity and wet-state structure stability, and is suitable for various airway hemostatic scenes such as post-bronchoscopy hemostasis, tracheal tube injury bleeding, post-lung transplantation anastomotic bleeding and nasal cavity surgery bleeding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical biomaterials technology, specifically to an airway hemostatic aerogel and its preparation method. Background Technology

[0002] Airway bleeding is a common complication in respiratory medicine, thoracic surgery, interventional bronchoscopy, and nasal interventional procedures. It mainly includes bleeding from the wound after bronchoscopy, bleeding from the surface of airway tumors, oozing from endotracheal intubation injuries, anastomotic bleeding after lung transplantation, bleeding from transnasal surgery, and traumatic airway bleeding. Currently, clinical treatment for airway bleeding primarily employs methods such as local drug infusion, balloon compression, and thermal coagulation, whose mechanisms of action rely on vasoconstriction, physical compression, or thermal coagulation. However, these methods all have significant limitations in clinical application, either failing to simultaneously achieve rapid hemostasis and maintain airway patency, or lacking sufficient wet mechanical strength and the ability to remove the material without damaging the wound. Therefore, there is an urgent need to develop a packing material with superior overall performance.

[0003] Ideal airway hemostatic materials should possess the following characteristics: maintaining airway ventilation while stopping bleeding; in addition, they should have good biocompatibility, rapid blood absorption capacity, appropriate water absorption and swelling to generate uniform pressure, sufficient wet mechanical strength to maintain the packing effect, compression resilience, no damage to the wound surface upon removal, and hemostatic, breathable, and antibacterial properties.

[0004] Specifically, existing clinical methods still have significant shortcomings in terms of overall performance. For example, balloon tamponade can directly compress the bleeding point, but the balloon cannot be left in place for long periods, and once inflated, it completely blocks ventilation, leading to poor patient tolerance and potential secondary injury during removal. Drug infusion, such as adrenaline or ice-cold saline, has limited effectiveness for deep bleeding and a short duration of action. Thermal coagulation, such as argon plasma coagulation, is ineffective for diffuse bleeding and may damage the airway mucosa.

[0005] In recent years, the local application of biomaterials for tamponade has gradually attracted attention. A mixture of absorbable gelatin and thrombin has been attempted to treat airway bleeding unresponsive to conventional methods, but its wet mechanical strength is insufficient, and its structure easily softens and deforms after absorbing blood, making it difficult to maintain effective pressure on the wound. Furthermore, softened alginate dressings may shift and obstruct the airway. While alginate dressings have good absorbency, their wet strength is insufficient to provide sustained mechanical support.

[0006] To address the performance deficiencies of the aforementioned materials, researchers have attempted to combine biodegradable materials with active substances to obtain composite materials that possess both mechanical support and hemostatic properties. Polylactic acid (PLA), a biodegradable material approved by the U.S. Food and Drug Administration (FDA), exhibits good biocompatibility and mechanical strength. However, PLA is highly hydrophobic and lacks hemostatic active sites, resulting in poor blood absorption when used alone as a hemostatic material. Silk fibroin promotes cell adhesion and accelerates the activation of intrinsic coagulation pathways, but pure silk fibroin materials soften easily in a wet state, providing insufficient mechanical support.

[0007] Document CN108421081A discloses an anti-infective, safe, and highly effective hemostatic aerogel and its preparation method. It is prepared by supercritical drying of chitosan grafted with 8-O-acetylglucosinolate methyl ester, sodium alginate, and gellan gum. While it exhibits good swelling and anti-infective properties, the mechanical support of its material system mainly relies on the polysaccharide cross-linking network, resulting in limited wet compressive strength and resilience, making it difficult to maintain stable packing compression in the dynamic environment of the airway. Document CN118767200A discloses a hemostatic aerogel and its preparation method, using hydrophilic and hydrophobic fibers to obtain a helical pore structure through shearing, freeze-drying, and cross-linking. However, it does not involve the loading of silk fibroin and active hemostatic components, and the pore structure cannot form continuous gas channels due to fiber severance, resulting in reduced air permeability.

[0008] Comprehensive analysis reveals that existing technologies for airway hemostatic materials still suffer from insufficient wet mechanical strength, easy airway blockage, and weak interfacial bonding. Achieving a uniform composite of hydrophobic polylactic acid and hydrophilic silk fibroin at the microscale, enabling both to synergistically provide mechanical support and coagulation functions while ensuring structural stability and ventilation in a wetted state, remains a critical technical challenge in the preparation of high-performance airway hemostatic materials.

[0009] To date, there are no reports on airway hemostatic aerogels that utilize polylactic acid fibers and silk fibroin fibers to form a three-dimensional porous network structure, disperse hemostatic materials within the silk fibroin fibers, and use inter-fiber binders to create a cross-linked network between the two types of fibers to enhance wet mechanical stability, while maintaining a continuous porous structure to preserve airway ventilation function even after absorbing water and swelling. Summary of the Invention

[0010] To overcome the shortcomings of the prior art, the present invention provides an airway hemostatic aerogel with excellent air permeability, rapid coagulation activity and wet structural stability, and a method for preparing the same.

[0011] To solve the above-mentioned technical problems, the solution of the present invention is: A hemostatic airway gel is provided, comprising: Polylactic acid fibers and silk fibroin fibers intertwine to form a three-dimensional porous network structure, and hemostatic materials are dispersed in the silk fibroin fibers; The aerogel also contains an inter-fiber binder that enables interlocking bonding points to be formed between the interwoven polylactic acid fibers and silk fibroin fibers, thereby enhancing the stability of the three-dimensional porous network structure.

[0012] Furthermore, the polylactic acid fiber has a diameter of 10~50 μm; the silk fibroin fiber has a diameter of 100~1000 nm; and the three-dimensional porous network has a pore size of 50~200 μm.

[0013] Furthermore, the hemostatic material is any one or a combination of two or more of the following: fibrinogen, hemostatic polypeptide, thrombin, zeolite, chitosan, calcium alginate, oxidized cellulose, and microporous polysaccharide.

[0014] Furthermore, the adhesive is any one or a combination of two or more of the following: methacrylamide gelatin, methacrylic acid gellan gum, methacrylamide keratin, methacrylamide hyaluronic acid, methacrylamide silk fibroin, and photocrosslinked alginate derivatives.

[0015] Furthermore, the aerogel has a porosity of 85% to 95%, a wet compressive strength of 1 to 10 kPa, and a water absorption swelling rate of 0 to 20%. After absorbing simulated blood equivalent to 10 to 20 times its own weight, its compression rebound rate can still be maintained at over 95%, and after absorbing water and swelling, it still maintains a permeable pore structure to maintain airway ventilation function.

[0016] A method for preparing the airway hemostatic aerogel according to any one of the above claims includes the following steps: Step (1): Dissolve polylactic acid to obtain spinning solution A; dissolve silk fibroin to obtain spinning solution B, and disperse the hemostatic material in spinning solution B; mix the adhesive and photoinitiator to obtain a photosensitive adhesive solution; Step (2): Inject the spinning solution A and spinning solution B described in step (1) into the spinneret to perform rotary jet spinning, and at the same time spray the photosensitive binder solution described in step (1) onto the fiber assembly, and obtain a pre-cured fiber assembly by ultraviolet irradiation; Step (3): Place the fiber assembly described in step (2) in a transparent mold for ultraviolet irradiation to obtain a preliminary aerogel; Step (4): The aerogel described in step (3) is placed in a genipin alcohol-water mixed solution for cross-linking reaction; Step (5): Soak the aerogel described in step (4) in ethanol aqueous solution with increasing volume fraction, then replace it with ethanol aqueous solution with decreasing volume fraction, and finally replace it with deionized water until the ethanol is completely removed, thus obtaining the airway hemostatic aerogel.

[0017] Further, in step (1), the concentration of the polylactic acid solution is 10%~20% (w / v); the concentration of the silk fibroin solution is 15%~25% (w / v); and the mass fraction of the hemostatic material is 1%~5%.

[0018] Further, in step (2), the adhesive concentration is 5%~15% (w / v), the photoinitiator is LAP with a concentration of 0.1%~1% (w / v), the ultraviolet light wavelength is 365~405 nm, and the light intensity is 1~50 mW·cm. -2 The droplet exposure time is 0.5~60 s.

[0019] Further, the conditions for rotary jet spinning in step (2) are: rotation speed 2000~5000 rpm, needle size 27~30G, receiving distance 10~30 cm, temperature 30~60℃, relative humidity 30%~50%; the volume ratio of polylactic acid solution to silk fibroin solution is (1~3):1.

[0020] Further, in the genipin alcohol-water mixed solution described in step (4), the mass fraction of genipin is 0.5%~1.5%, the volume ratio of ethanol to water is (1:1)~(3:1); the crosslinking temperature is 40~55℃, and the crosslinking time is 2~6 hours.

[0021] Further, in step (5), the volume fraction of the ethanol aqueous solution increases by 30%, 50%, 70%, 90%, and 100%, and the soaking time for each step is 1 to 4 hours; the volume fraction of the ethanol aqueous solution decreases by 90%, 70%, 50%, and 30%, and the soaking time for each step is 1 to 4 hours.

[0022] The beneficial effects of this invention are: (1) The present invention uses polylactic acid fiber and silk fibroin fiber to form a three-dimensional network structure, and introduces interlocking bonding points between fibers to form a stable cross-linked network, which significantly improves the mechanical stability of aerogel in a humid environment. The continuity of long fibers can ensure air permeability, while giving the material good biocompatibility.

[0023] (2) The three-dimensional porous network constructed by interwoven fibers in this invention has high porosity and excellent wet resilience. Combined with low water absorption and expansion characteristics, it can adapt to the dynamic expansion and contraction environment of the airway, maintain structural integrity, ensure smooth gas flow, and prevent airway blockage caused by water absorption and expansion.

[0024] (3) The hemostatic material of the present invention is uniformly dispersed in silk fibroin fibers. With the help of the high specific surface area of ​​the nanofiber network, it can quickly absorb blood moisture and activate coagulation factors to achieve efficient and long-lasting local hemostasis. Moreover, the material is flexible and resilient, which is convenient for minimally invasive implantation and close fit to irregular wound surfaces. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the preparation process of the airway hemostatic aerogel of the present invention; Figure 2 This is a physical image of the airway hemostatic aerogel in Embodiment 1 of the present invention; Figure 3 This is a scanning electron microscope (SEM) image of the airway hemostatic aerogel in Embodiment 1 of the present invention; Figure 4 This is the stress-strain curve of the airway hemostatic aerogel in Embodiment 1 of the present invention; Figure 5 This refers to the wet compression resilience of the airway hemostatic aerogel in Embodiment 1 of the present invention; wherein... Figure 5 a is a photograph of the actual recovery of the dry aerogel after 50% compressive strain. Figure 5 b represents the load-unload curve after 5 cycles. Figure 5 c. Visually demonstrates the progressive deformation of the material in PBS solution at 20%, 40%, and 60% compressive strain. Figure 5 d represents the stable mechanical output result that can be maintained under different strain amplitudes.

[0027] Figure 6 This is an in vitro coagulation experiment of the airway hemostatic aerogel in Embodiment 1 of the present invention. Detailed Implementation

[0028] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments and accompanying drawings. The content mentioned in the embodiments is not intended to limit the present invention.

[0029] like Figure 1 As shown, the present invention provides a method for preparing airway hemostatic aerogel, comprising the following steps: Step (1): Dissolve polylactic acid to obtain spinning solution A; dissolve silk fibroin to obtain spinning solution B, and disperse the hemostatic material in spinning solution B; mix the adhesive and photoinitiator to obtain a photosensitive adhesive solution; Step (2): Inject the spinning solution A and spinning solution B described in step (1) into the spinneret to perform rotary jet spinning, and at the same time spray the photosensitive binder solution described in step (1) onto the fiber assembly, and obtain the pre-cured fiber assembly by ultraviolet irradiation; Step (3): Place the fiber assembly described in step (2) in a transparent mold for ultraviolet irradiation to obtain a preliminary aerogel; Step (4): The aerogel described in step (3) is placed in a genipin alcohol-water mixed solution for cross-linking reaction; Step (5): Soak the aerogel described in step (4) in ethanol aqueous solution with increasing volume fraction, then replace it with ethanol aqueous solution with decreasing volume fraction, and finally replace it with deionized water until the ethanol is completely removed, thus obtaining the airway hemostatic aerogel.

[0030] The following examples provide further details.

[0031] Example 1: Prepare spinning solution A by dissolving PLA (molecular weight 100 kDa) in hexafluoroisopropanol (HFIP) to prepare a 10% (w / v) solution. Prepare spinning solution B by dissolving silk fibroin in formic acid / water (8:2, v / v) to prepare a 15% (w / v) solution, add fibrinogen (mass fraction 1%) as a hemostatic material, and sonicate (200 W, 10 min). Prepare a photosensitive adhesive solution by dissolving methacryloyl gelatin (GelMA) in PBS (pH 7.4) containing 0.1% (w / v) LAP to prepare a 5% (w / v) solution. Prepare a genipin crosslinking solution with a genipin mass fraction of 0.5% and an ethanol to water volume ratio of 1:1. Use rotary jet spinning with the following parameters: spin speed 2000 rpm, needle size 30 G, receiving distance 10 cm, temperature 30℃, relative humidity 30%, and spinning solution A to B volume ratio 1:1. During the spinning process, the binder solution is sprayed at a rate of 0.5 mL / min, while simultaneously using 365 nm ultraviolet light (light intensity 1 mW·cm). -2 Pre-cured fiber assemblies were obtained by irradiation with a droplet exposure time of 0.5 s. The fiber assemblies were then placed in a transparent mold and subjected to secondary ultraviolet irradiation (365 nm, 10 mW·cm⁻¹). -2 The aerogel was then immersed in genipin crosslinking solution and crosslinked at 40°C for 2 hours. After crosslinking, it was soaked in 30%, 50%, 70%, 90%, and 100% ethanol aqueous solutions for 1 hour each, then in 90%, 70%, 50%, and 30% ethanol aqueous solutions for 1 hour each, and finally in deionized water for 2 hours (changing the water every hour). The sample was frozen at -20°C for 12 hours and then freeze-dried (-50°C, 0.1 mbar, 48 hours) to obtain airway hemostatic aerogel.

[0032] Test results: PLA fiber diameter 10 μm, silk fibroin fiber diameter 1000 nm, pore size 50 μm; porosity 85%; wet compressive strength 1.0 kPa; water absorption swelling rate 0%; wet compression resilience 96%. Air permeability: dry air permeability 880 mm / s, wet air permeability 520 mm / s (retention rate 59%), simulated airway tamping (5 L / min) increased wet pressure differential by 32 Pa.

[0033] Example 2: This embodiment is basically the same as Embodiment 1, except that the PLA solution concentration is adjusted to 20% (w / v), the silk fibroin solution concentration is adjusted to 25% (w / v), the hemostatic material is thrombin with a mass fraction of 5%, the binder is methacrylamide keratin with a concentration of 15% (w / v), and the LAP concentration is adjusted to 1% (w / v). The spinning parameters are: rotation speed 5000 rpm, needle size 27 G, receiving distance 30 cm, temperature 60℃, relative humidity 50%, and spinning solution A to B volume ratio 3:1. The binder spraying rate is 1.5 mL / min, the ultraviolet wavelength is 405 nm, and the light intensity is 50 mW·cm². -2 The droplet exposure time was 60 s. Secondary UV irradiation conditions were 405 nm, 20 mW·cm⁻², and 20 min. Genipin crosslinking conditions were 1.5% genipin by mass, ethanol to water volume ratio of 3:1, crosslinking temperature of 55℃, and crosslinking time of 6 h. Gradient solvent replacement was performed with 4 h immersion in each step.

[0034] Test results: PLA fiber diameter 50 μm, silk fibroin fiber 100 nm, pore size 200 μm; porosity 95%; wet compressive strength 10.0 kPa; water absorption swelling rate 20%; wet compression resilience 97%. Air permeability: dry air permeability 1520 mm / s, wet air permeability 810 mm / s (retention rate 53%), simulated airway tamping increased wet pressure differential by 28 Pa.

[0035] Example 3: This embodiment is basically the same as Embodiment 1, except that the PLA solution concentration is 15% (w / v), the silk fibroin solution concentration is 20% (w / v), the hemostatic material is chitosan with a mass fraction of 2.5%, the binder is methacryloyl hyaluronic acid with a concentration of 10% (w / v), and the LAP concentration is adjusted to 0.5% (w / v). The spinning parameters are: rotation speed 3500 rpm, needle size 29 G, receiving distance 20 cm, temperature 45℃, relative humidity 40%, and spinning solution A to B volume ratio 2:1. The ultraviolet light wavelength is 385 nm, and the light intensity is 25 mW·cm². -2The droplet exposure time was 30 s. The secondary UV irradiation conditions were 385 nm and 15 mW·cm⁻¹. -2 The genipin crosslinking conditions were 1.0% genipin by mass, 2:1 ethanol to water by volume, 48℃ crosslinking temperature, and 4 h crosslinking time. Gradient solvent replacement was performed with 2 h immersion in each step.

[0036] Test results: PLA fiber diameter 30 μm, silk fibroin fiber 500 nm, pore size 120 μm; porosity 90%; wet compressive strength 5.5 kPa; water absorption swelling rate 10%; wet compression resilience 98%. Air permeability: dry air permeability 1120 mm / s, wet air permeability 610 mm / s (retention rate 54%), simulated airway tamping wet pressure difference increased by 35 Pa.

[0037] Example 4: This embodiment is basically the same as Example 3, except that the hemostatic material is RGD-modified hemostatic polypeptide with a mass fraction of 3%, and the binder is methacrylamide silk fibroin with a concentration of 8% (w / v).

[0038] Test results: PLA fiber diameter 28 μm, silk fibroin fiber 480 nm, pore size 115 μm; porosity 88%; wet compressive strength 4.2 kPa; water absorption swelling rate 5%; wet compression resilience 97%. Air permeability: dry air permeability 1050 mm / s, wet air permeability 580 mm / s (retention rate 55%), simulated airway tamping increased wet pressure differential by 36 Pa.

[0039] Example 5: This embodiment is basically the same as embodiment 3, except that the hemostatic material is zeolite micro powder (particle size 1~3 μm) with a mass fraction of 4%, and the binder is replaced with methacrylamide gelatin with a concentration of 12% (w / v).

[0040] Test results: Porosity 92%; wet compressive strength 6.8 kPa; water absorption swelling rate 12%; wet compression rebound rate 96%. Air permeability: dry air permeability 1300 mm / s, wet air permeability 680 mm / s (retention rate 52%), simulated airway tamping wet pressure difference increased by 31 Pa.

[0041] Example 6: This embodiment is basically the same as embodiment 3, except that the hemostatic material is calcium alginate with a mass fraction of 2%, and the binder is a photocrosslinked alginate derivative with a concentration of 10% (w / v).

[0042] Test results: Porosity 87%; wet compressive strength 3.5 kPa; water absorption swelling rate 2%; wet compression rebound rate 95%. Air permeability: dry air permeability 780 mm / s, wet air permeability 430 mm / s (retention rate 55%), simulated airway tamping wet pressure difference increased by 42 Pa.

[0043] Example 7: This embodiment is basically the same as Embodiment 3, except that the hemostatic material is oxidized cellulose with a mass fraction of 5%, and the binder is gellan methacrylate with a concentration of 10% (w / v).

[0044] Test results: Porosity 90%; wet compressive strength 7.2 kPa; water absorption swelling rate 15%; wet compression rebound rate 97%. Air permeability: dry air permeability 1180 mm / s, wet air permeability 620 mm / s (retention rate 53%), simulated airway tamping wet pressure difference increased by 33 Pa.

[0045] Example 8: This embodiment is basically the same as Embodiment 3, except that the hemostatic material is microporous polysaccharide (cross-linked dextran microspheres) with a mass fraction of 3%, and the binder is methacrylamide keratin with a concentration of 10% (w / v).

[0046] Test results: Porosity 93%; wet compressive strength 5.0 kPa; water absorption swelling rate 8%; wet compression rebound rate 98%. Air permeability: dry air permeability 1420 mm / s, wet air permeability 750 mm / s (retention rate 53%), simulated airway tamping wet pressure difference increased by 29 Pa.

[0047] Example 9: This embodiment is basically the same as Embodiment 3, except that the hemostatic material is a mixture of fibrinogen and thrombin (mass ratio 1:1) with a total mass fraction of 3%, and the binder is methacrylamide hyaluronic acid with a concentration of 12% (w / v).

[0048] Test results: Porosity 91%; wet compressive strength 8.5 kPa; water absorption swelling rate 18%; wet compression rebound rate 96%. Air permeability: dry air permeability 1250 mm / s, wet air permeability 640 mm / s (retention rate 51%), simulated airway tamping wet pressure difference increased by 34 Pa.

[0049] Example 10: This embodiment is basically the same as Embodiment 3, except that the hemostatic material is a mixture of chitosan and calcium alginate (mass ratio 2:1), with a total mass fraction of 4%, and the binder is methacrylamide silk fibroin with a concentration of 10% (w / v).

[0050] Test results: Porosity 89%; wet compressive strength 6.0 kPa; water absorption swelling rate 6%; wet compression rebound rate 97%. Air permeability: dry air permeability 1080 mm / s, wet air permeability 590 mm / s (retention rate 55%), simulated airway tamping wet pressure difference increased by 36 Pa.

[0051] Example 11: This embodiment is basically the same as embodiment 3, except that the adhesive is a mixture of equal mass of methacrylamide gelatin and methacrylamide keratin with a total concentration of 10% (w / v), and the hemostatic material is thrombin with a mass fraction of 2%.

[0052] Test results: Porosity 91%; wet compressive strength 7.8 kPa; water absorption swelling rate 12%; wet compression rebound rate 96%. Air permeability: dry air permeability 1260 mm / s, wet air permeability 660 mm / s (retention rate 52%), simulated airway tamping wet pressure difference increased by 32 Pa.

[0053] Example 12: This embodiment is basically the same as Example 3, except that the crosslinking time of genipin is 2 h, 4 h and 6 h respectively.

[0054] Test results: After 2 hours of crosslinking, the porosity was 91%; wet compressive strength was 4.1 kPa; water absorption swelling rate was 8%; and wet compression resilience was 96%. Air permeability: dry air permeability was 1150 mm / s, wet air permeability was 630 mm / s (retention rate 55%), and the wet pressure difference increased by 34 Pa. After 4 hours of crosslinking, the porosity was 90%; wet compressive strength was 5.8 kPa; water absorption swelling rate was 10%; and wet compression resilience was 97%. Air permeability: dry air permeability was 1120 mm / s, wet air permeability was 610 mm / s (retention rate 54%), and the wet pressure difference increased by 35 Pa. After 6 hours of crosslinking, the porosity was 89%; wet compressive strength was 7.5 kPa; water absorption swelling rate was 19%; and wet compression resilience was 95%. Ventilation performance: Dry air permeability 1050 mm / s, wet air permeability 540 mm / s (retention rate 51%), wet pressure difference increase 39 Pa.

[0055] Example 13: This embodiment is basically the same as embodiment 3, except that the concentrations of silk fibroin are 15%, 20% and 25%, respectively.

[0056] Test results: At a concentration of 15%, the silk fibroin fiber diameter is 350 nm, porosity is 92%; wet compressive strength is 3.8 kPa; water absorption swelling rate is 5%; resilience is 96%. Air permeability: dry air permeability is 1350 mm / s, wet air permeability is 720 mm / s (retention rate 53%), wet pressure difference increases by 30 Pa. At a concentration of 20%, the silk fibroin fiber diameter is 500 nm, porosity is 90%; wet compressive strength is 5.5 kPa; water absorption swelling rate is 10%; resilience is 98%. Air permeability: dry air permeability is 1120 mm / s, wet air permeability is 610 mm / s (retention rate 54%), wet pressure difference increases by 35 Pa. At a concentration of 25%, the silk fibroin fiber diameter is 800 nm, porosity is 88%; wet compressive strength is 7.0 kPa; water absorption swelling rate is 14%; resilience is 97%. Ventilation performance: Dry air permeability 960 mm / s, wet air permeability 490 mm / s (retention rate 51%), wet pressure difference increase 41 Pa.

[0057] Example 14: This embodiment is basically the same as embodiment 3, except that the mass fraction of the hemostatic material (fibrinogen) is 1%, 3% and 5%, respectively.

[0058] Test results: At 1%, porosity is 91%; wet compressive strength is 5.8 kPa; water absorption swelling rate is 9%; resilience is 97%. Air permeability: dry air permeability is 1140 mm / s, wet air permeability is 620 mm / s (retention rate 54%), wet pressure difference increases by 34 Pa. At 3%, porosity is 90%; wet compressive strength is 5.5 kPa; water absorption swelling rate is 10%; resilience is 98%. Air permeability: dry air permeability is 1120 mm / s, wet air permeability is 610 mm / s (retention rate 54%), wet pressure difference increases by 35 Pa. At 5%, porosity is 86%; wet compressive strength is 4.5 kPa; water absorption swelling rate is 11%; resilience is 96%. Air permeability: dry air permeability is 900 mm / s, wet air permeability is 470 mm / s (retention rate 52%), wet pressure difference increases by 43 Pa.

[0059] Example 15: This embodiment is basically the same as embodiment 3, except that the volume ratio of spinning solution A to spinning solution B is 1:1, 2:1 and 3:1 respectively.

[0060] Test results: At a 1:1 ratio, porosity is 90%; wet compressive strength is 5.5 kPa; water absorption swelling rate is 10%; resilience is 98%. Air permeability: dry air permeability is 1120 mm / s, wet air permeability is 610 mm / s (retention rate 54%), wet pressure difference increases by 35 Pa. At a 2:1 ratio, porosity is 89%; wet compressive strength is 7.2 kPa; water absorption swelling rate is 6%; resilience is 97%. Air permeability: dry air permeability is 1060 mm / s, wet air permeability is 580 mm / s (retention rate 55%), wet pressure difference increases by 36 Pa. At a 3:1 ratio, porosity is 87%; wet compressive strength is 8.8 kPa; water absorption swelling rate is 4%; resilience is 92% (below 95%). Ventilation performance: Dry air permeability 950 mm / s, wet air permeability 480 mm / s (retention rate 51%), wet pressure difference increase 44 Pa.

[0061] Example 16: This embodiment is basically the same as Embodiment 3, except that the ultraviolet light intensity during the spinning process is 1, 25, and 50 mW·cm, respectively. -2 The corresponding droplet exposure times were 0.5, 30, and 60 s, respectively.

[0062] Test Results: Low Light Intensity / Short Exposure: Porosity 92%; Wet Compressive Strength 2.5 kPa; Water Absorption Swelling Rate 12%; Resilience 90%. Air Permeability: Dry Air Permeability 1380 mm / s, Wet Air Permeability 710 mm / s (Retention Rate 51%), Wet Pressure Difference Increase 31 Pa. Medium Light Intensity / Medium Exposure: Porosity 90%; Wet Compressive Strength 5.8 kPa; Water Absorption Swelling Rate 10%; Resilience 98%. Air Permeability: Dry Air Permeability 1120 mm / s, Wet Air Permeability 610 mm / s (Retention Rate 54%), Wet Pressure Difference Increase 35 Pa. High Light Intensity / Long Exposure: Porosity 88%; Wet Compressive Strength 6.9 kPa; Water Absorption Swelling Rate 9%; Resilience 88%. Ventilation performance: Dry air permeability 1000 mm / s, wet air permeability 500 mm / s (retention rate 50%), wet pressure difference increase 40 Pa.

[0063] Example 17: This embodiment is basically the same as embodiment 3, except that different types of adhesives are used (both with a concentration of 10%, and the hemostatic material is chitosan 3%).

[0064] Test results: GelMA: Porosity 90%; Strength 5.5 kPa; Expansion rate 10%; Resilience 97%. Dry air permeability 1120 mm / s, wet air permeability 610 mm / s (retention rate 54%), pressure difference 35 Pa.

[0065] Gellan methacrylate: Porosity 89%; Strength 5.2 kPa; Expansion rate 9%; Resilience 96%. Dry air permeability 1080 mm / s, wet air permeability 580 mm / s (retention rate 54%), pressure difference 36 Pa.

[0066] Methacrylamide keratin: Porosity 91%; Strength 6.2 kPa; Expansion rate 11%; Resilience 97%. Dry air permeability 1150 mm / s, wet air permeability 620 mm / s (retention rate 54%), pressure difference 34 Pa.

[0067] Methacrylamide hyaluronic acid: porosity 90%; strength 4.8 kPa; expansion rate 10%; resilience 96%. Dry air permeability 1100 mm / s, wet air permeability 590 mm / s (retention rate 54%), pressure difference 36 Pa.

[0068] Methacrylamide silk fibroin: porosity 89%; strength 5.0 kPa; expansion rate 9%; resilience 97%. Dry air permeability 1060 mm / s, wet air permeability 560 mm / s (retention rate 53%), pressure difference 38 Pa.

[0069] Photocrosslinked alginate derivative: porosity 88%; strength 3.9 kPa; expansion rate 8%; resilience 95%. Dry air permeability 920 mm / s, wet air permeability 470 mm / s (retention rate 51%), pressure difference 44 Pa.

[0070] Example 18: This embodiment is basically the same as Example 3, except that the genipin crosslinking temperatures are 40°C, 48°C and 55°C, and the genipin concentrations are 0.5%, 1.0% and 1.5%, respectively.

[0071] Test results: 40℃ / 0.5%: Strength 4.2 kPa; Expansion rate 7%; Resilience rate 95%. Dry air permeability 1080 mm / s, wet air permeability 570 mm / s (retention rate 53%), pressure difference 37 Pa.

[0072] 48℃ / 1.0%: Strength 6.1 kPa; Expansion rate 12%; Resilience 97%. Dry air permeability 1120 mm / s, wet air permeability 610 mm / s (retention rate 54%), pressure difference 35 Pa.

[0073] 55℃ / 1.5%: Strength 7.8 kPa; Expansion rate 20%; Resilience 94%. Dry air permeability 1000 mm / s, wet air permeability 500 mm / s (retention rate 50%), pressure difference 42 Pa.

[0074] Morphological characterization and performance testing were performed on the above embodiments: 1. Appearance and morphology characterization: The appearance of the airway hemostatic aerogel prepared in Example 1 was recorded using a digital camera, such as... Figure 2 As shown, the aerogel is in block form, with a loose and uniform texture and clear, intact edges, facilitating clinical cutting and bronchoscopic delivery. Airway hemostatic aerogels prepared in other embodiments exhibit similar properties.

[0075] 2. Microscopic Morphology Characterization: The microscopic morphology of the airway hemostatic aerogel prepared in Example 1 was observed using scanning electron microscopy (SEM), such as... Figure 3 As shown in the SEM images, polylactic acid microfibers (10–50 μm in diameter) and silk fibroin nanofibers (100–1000 nm in diameter) interweave to form a three-dimensional porous network structure with pore sizes of 50–200 μm. Interlocking bonding points formed by UV cross-linking of photosensitive adhesives between the fibers are visible, effectively enhancing the structural integrity of the fiber aggregate. The relatively rough pore wall surface facilitates the adhesion and anchoring of blood cells, while the interconnected porous structure retains sufficient channels for gas exchange. Fiber diameter and pore size data were obtained through statistical measurement of the fibers and pores in the SEM images. Airway hemostatic aerogels prepared in other embodiments exhibit similar properties.

[0076] 3. Porosity determination: The total porosity was directly determined using a mercury porosimeter by measuring the volume of mercury entering the pores under different pressures. The test results of Examples 1-18 show that the porosity of this aerogel is 85%-95%, confirming its high porosity characteristic.

[0077] 4. Mechanical property testing: The fracture strength of the aerogel was tested using a universal testing machine. The sample was stretched at a rate of 1 mm / min until it completely fractured, and the stress-strain curve was recorded. Figure 4 As shown, the aerogel prepared in Example 1 did not show a clear yield point during compression. As the strain increased, the stress first rose rapidly to a peak value and then gradually decreased. The peak stress was about 1.9 MPa, indicating that the aerogel has good strength and mechanical stability.

[0078] 5. Dry / Wet Compression Resilience Test: After immersing the aerogel sample in PBS until equilibrium, multiple cyclic loading-unloading compression tests were performed using a universal testing machine. The stress-strain curves for each cycle were recorded, and the resilience rate was calculated. Taking the aerogel prepared in Example 1 as an example... Figure 5 a is a photograph of the dry aerogel after 50% compressive strain recovery. The sample has a complete shape and no obvious damage, indicating that the material has good structural integrity in the air environment. Figure 5b represents the loading-unloading curves for 5 cycles. The curves basically overlap, and no obvious hysteresis loop shift or peak stress attenuation is observed, which confirms that the material has excellent fatigue resistance and dynamic deformation stability. Figure 5 c. Visually demonstrate the progressive deformation of the material under 20%, 40%, and 60% compressive strain in PBS solution, reflecting its good compressive compliance and shape adaptability; Figure 5 Further verification showed that the material maintained stable mechanical output under different strain amplitudes, proving its reliable rebound capability over a wide strain range. Test results from Examples 1-18 show a wet compression rebound rate of 95%-98%, confirming that the aerogel can maintain its packing effect for a long time without fatigue collapse in the cyclical expansion and contraction environment of the airway. The test results from Examples 1-18 also show a wet compression rebound rate as high as 95%-98%, indicating that the aerogel can dynamically deform with the cyclical expansion and contraction of the airway without fatigue collapse.

[0079] 6. Determination of water absorption and swelling rate: Weigh the dried aerogel (denoted as W0) and measure its geometric volume (denoted as V0). Immerse it in PBS or simulated blood until it is saturated with water (37°C, 24 h). After removal, absorb excess liquid on the surface with filter paper, weigh it (denoted as W1), and measure its volume (denoted as V1). Calculate the water absorption rate (%) using the formulas: Water absorption rate (%) = (W1 - W0) / W0 × 100%, Swelling rate (%) = (V1 - V0) / V0 × 100%. The test results of Examples 1-18 show that the water absorption and swelling rate is 0%~20%, indicating that the aerogel has a small volume change after absorbing water, which can effectively avoid excessive expansion compressing the airway wall or blocking the lumen.

[0080] 7. In vitro coagulation test: Fresh anticoagulated rabbit blood was dropped onto the surface of the aerogel sample (3 parallel samples per group). After incubation at 37℃ for a certain time (e.g., 5 min, 10 min), the blood coagulation state was observed, and the sample was gently rinsed with deionized water to assess the stability of the blood clot. Taking the aerogel prepared in Example 1 as an example, as... Figure 6 As shown on the left, after the aerogel containing hemostatic materials (fibrinogen, thrombin, chitosan, etc.) came into contact with blood, the blood rapidly transformed from a liquid state into a gel-like blood clot with a uniform dark red color, indicating that the coagulation process was complete. On the right, after gentle rinsing with deionized water, the blood clot remained firmly attached to the fiber network of the material, without being washed away or detached, confirming that the aerogel has rapid coagulation ability and that the blood clot is stably bound to the material. This test, by comparing a blank control group (aerogel without hemostatic materials) and an experimental group, verified the crucial role of the hemostatic active ingredients dispersed in silk fibroin fibers in accelerating coagulation. Examples 1-18 used different hemostatic materials and formulations, but all showed good coagulation effects.

[0081] 8. Ventilation Performance Test: The sample was placed on a permeability tester, and the airflow rate passing through a unit area of ​​the sample per unit time was measured under a constant pressure difference to obtain the dry permeability. After the sample was moistened with PBS or simulated blood, the wet permeability was measured under the same conditions, and the wet permeability retention rate (%) was calculated as (wet permeability / dry permeability) × 100%. Simultaneously, a simulated airway tamponade model was used, and the pressure difference change before and after tamponade was measured under an airflow of 5 L / min. The test results of Example 1 showed that the dry permeability was 880 mm / s, the wet permeability was 520 mm / s (retention rate 59%), and the increase in wet pressure difference under simulated airway tamponade was only 32 Pa, indicating that the aerogel can maintain good gas permeability even under blood-absorbing and moistened conditions and will not cause airway obstruction.

[0082] Comparative Example 1: This comparative example is basically the same as Example 3, except that no binder solution is sprayed during the spinning process and no ultraviolet irradiation is performed.

[0083] Test results: The obtained fiber aggregates were loose and unable to support themselves. After genipin crosslinking and freeze-drying, the product immediately disintegrated upon contact with water, with a wet compressive strength of less than 0.1 kPa, making it impossible to measure porosity, water absorption swelling rate, and resilience. Air permeability: Dry air permeability was 1850 mm / s (loose fibers), but the structure collapsed in the wet state, failing to maintain stable airflow, making the wet air permeability unmeasurable. The simulated airway clogging wet pressure difference was >200 Pa.

[0084] Comparative Example 2: This comparative example is basically the same as Example 3, except that the genipin crosslinking step is omitted.

[0085] Test results: Water absorption swelling rate reached 45% (exceeding the 20% upper limit); wet compression rebound rate was only 72% (below 95%); porosity decreased to 78%; wet compressive strength was 0.4 kPa. Air permeability: dry air permeability 1350 mm / s, wet air permeability 320 mm / s (retention rate 24%), simulated airway tamping wet pressure difference increased by 98 Pa (exceeding the 50 Pa threshold).

[0086] Comparative Example 3: This comparative example uses a sequential spinning method: first, a PLA fiber layer (2 mm thick) is collected using the parameters of Example 3, and then a silk fibroin fiber layer (2 mm thick) is collected on the same receiver. The two layers are stacked but not interwoven. Subsequent steps such as binder spraying, ultraviolet irradiation, and genipin crosslinking are the same as in Example 3.

[0087] Test results: Poor interlayer bonding, wet compressive strength only 0.8 kPa; water absorption swelling rate 35%; wet compression rebound rate 65%; porosity 82%. Air permeability: dry air permeability 960 mm / s, wet air permeability 310 mm / s (retention rate 32%), simulated airway tamping wet pressure difference increased by 115 Pa.

[0088] Comparative Example 4: This comparative example is basically the same as Example 3, except that an aerogel without hemostatic material is prepared first according to the method of Example 3 (i.e., chitosan is not added to spinning solution B), and then the finished aerogel is soaked in a 2.5% (w / v) chitosan aqueous solution for 12 h, taken out and freeze-dried, so that the hemostatic material is adsorbed on the fiber surface.

[0089] Test results: Initial wet compressive strength 5.2 kPa, water absorption swelling rate 11%, resilience 96%; however, after soaking, the surface chitosan easily detached, the water absorption swelling rate increased to 25%, and the resilience decreased to 85%. Air permeability: Initial dry air permeability 1100 mm / s, wet air permeability 610 mm / s (retention rate 55%); after detachment, the wet air permeability decreased to 380 mm / s (retention rate 35%), and the wet pressure difference increased by 76 Pa.

[0090] Comparative Example 5: This comparative example is basically the same as Example 3, except that the porosity is reduced to 80% by increasing the spinning time and increasing the fiber packing density.

[0091] Test results: Wet compressive strength 12.5 kPa (10 kPa higher than the upper limit of the claims), water absorption swelling rate 28% (exceeding 20%), wet compression rebound rate 82% (below 95%). Ventilation performance: Dry air permeability 650 mm / s, wet air permeability 220 mm / s (retention rate 34%), simulated airway tamping wet pressure difference increased by 92 Pa.

[0092] Comparative Example 6: This comparative example is basically the same as Example 3, except that a common gelatin aqueous solution (10%, w / v, without methacryloyl groups, without added LAP) is used instead of a photosensitive adhesive, and no ultraviolet irradiation is performed.

[0093] Test results: Gelatin underwent severe swelling and dissolution during ethanol gradient replacement and genipin crosslinking, resulting in loss of inter-fiber bonding and the inability to form the final product. The wet compressive strength was <0.2 kPa. Air permeability: Dry air permeability could not be accurately measured (due to uneven fiber clumps), and the product was completely blocked in the wet state, with no effective air permeability.

[0094] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present technical solution are within the protection scope of the present invention.

[0095] To facilitate understanding by those skilled in the art of the improvements of this invention over the prior art, some of the accompanying drawings and descriptions have been simplified, and for clarity, some other elements have been omitted from this application. Those skilled in the art should realize that these omitted elements may also constitute the content of this invention.

Claims

1. An airway hemostatic aerogel, characterized in that, include: Polylactic acid fibers and silk fibroin fibers intertwine to form a three-dimensional porous network structure, and hemostatic materials are dispersed in the silk fibroin fibers; The aerogel also contains an inter-fiber binder that enables interlocking bonding points to be formed between the interwoven polylactic acid fibers and silk fibroin fibers, thereby enhancing the stability of the three-dimensional porous network structure.

2. The airway hemostatic aerogel according to claim 1, characterized in that, The polylactic acid fiber has a diameter of 10~50 μm; the silk fibroin fiber has a diameter of 100~1000 nm; and the three-dimensional porous network has a pore size of 50~200 μm.

3. The airway hemostatic aerogel according to claim 1, characterized in that, The hemostatic material is any one or more of fibrinogen, hemostatic polypeptide, thrombin, zeolite, chitosan, calcium alginate, oxidized cellulose, and microporous polysaccharide.

4. The airway hemostatic aerogel according to claim 1, characterized in that, The adhesive is any one or more of the following: methacrylamide gelatin, methacrylamide gellan gum, methacrylamide keratin, methacrylamide hyaluronic acid, methacrylamide silk fibroin, and photocrosslinked alginate derivatives.

5. The airway hemostatic aerogel according to any one of claims 1 to 4, characterized in that, The aerogel has a porosity of 85%~95%, a wet compressive strength of 1~10 kPa, a water absorption swelling rate of 0%~20%, and a wet compression resilience of 95%~98%.

6. A method for preparing the airway hemostatic aerogel as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Step (1): Dissolve polylactic acid to obtain spinning solution A; Silk fibroin and hemostatic material were dissolved to obtain spinning solution B; adhesive and photoinitiator were mixed to obtain photosensitive adhesive solution; Step (2): Inject the spinning solution A and spinning solution B described in step (1) into the spinneret to perform rotary jet spinning, and at the same time spray the photosensitive binder solution described in step (1) onto the fiber assembly, and obtain the pre-cured fiber assembly by ultraviolet irradiation; Step (3): Place the fiber assembly described in step (2) in a transparent mold for ultraviolet irradiation to obtain a preliminary aerogel; Step (4): The aerogel described in step (3) is placed in a genipin alcohol-water mixed solution for cross-linking reaction; Step (5): Soak the aerogel described in step (4) in ethanol aqueous solution with increasing volume fraction, then replace it with ethanol aqueous solution with decreasing volume fraction, and finally replace it with deionized water until the ethanol is completely removed, thus obtaining the airway hemostatic aerogel.

7. The method for preparing the airway hemostatic aerogel according to claim 6, characterized in that, The concentration of the polylactic acid solution in step (1) is 10%~20% (w / v); the concentration of the silk fibroin solution is 15%~25% (w / v); and the mass fraction of the hemostatic material is 1%~5%.

8. The method for preparing the airway hemostatic aerogel according to claim 6, characterized in that, The adhesive concentration in step (2) is 5%~15% (w / v), the photoinitiator is LAP with a concentration of 0.1%~1% (w / v), the ultraviolet light wavelength is 365~405 nm, and the light intensity is 1~50 mW·cm. -2 The droplet exposure time is 0.5~60 s.

9. The method for preparing the airway hemostatic aerogel according to claim 6, characterized in that, The conditions for rotary jet spinning in step (2) are: rotation speed 2000~5000 rpm, needle size 27~30 G, receiving distance 10~30 cm, temperature 30~60℃, relative humidity 30%~50%; the volume ratio of polylactic acid solution to silk fibroin solution is (1~3):

1.

10. The method for preparing the airway hemostatic aerogel according to claim 6, characterized in that, In step (4), the genipin alcohol-water mixed solution has a genipin mass fraction of 0.5% to 1.5%, and an ethanol to water volume ratio of (1:1) to (3:1); the crosslinking temperature is 40 to 55°C, and the crosslinking time is 2 to 6 hours.

11. The method for preparing the airway hemostatic aerogel according to claim 6, characterized in that, In step (5), the volume fraction of the ethanol aqueous solution increases by 30%, 50%, 70%, 90%, and 100%, and the soaking time for each step is 1 to 4 hours; the volume fraction of the ethanol aqueous solution decreases by 90%, 70%, 50%, and 30%, and the soaking time for each step is 1 to 4 hours.

Citation Information

Patent Citations

  • Anti-infective, safe and efficient hemostatic aerogel and preparation method thereof

    CN108421081A

  • Hemostatic aerogel and preparation method thereof

    CN118767200A